Plant facilitation shifts along with soil moisture and phosphorus gradients via rhizosphere interaction in the maize-grass pea intercropping system. (June 2022) - Zhu, Shuang-Guo; Cheng, Zheng-Guo; Batool, Asfa; Wang, Yi-Bo; Wang, Jing; Zhou, Rui; Khan, Aziz; Zhu, Sai-Yong; Yang, Yu-Miao; Wang, Wei; Zhu, Hao; Wang, Bao-Zhong; et al.
Graphical abstract: Note: P (phosphorus), W (water), + (positive or increase), – (negative or decrease). Highlights: Plant facilitation was found in the intercropping system of maize and grass pea. Facilitation shifted from +/+, +/0 to +/- from low to high water and P gradients. In low P, rhizosphere soil acidification of grass pea fostered P mineralization. Soil microbial biomass P was improved for higher productivity in +/+ facilitation. Soil water and phosphorus availability altered interspecific facilitation model. Abstract: Plant-plant facilitation is widely studied to increase productivity and resource utilization in cereal-legume intercropping system. However, physiological and ecological mechanisms driving interspecific interaction shift along the environmental gradients is largely unknown. To clarify this issue, we first tested plant-plant facilitation along with four phosphorus (P) gradients in maize-grass pea intercropping system. Results illustrated a progressive transition of seed yield-based facilitation from mutually facilitated (+/+) to maize facilitated but grass pea as facilitator (+/-) along with low to high P gradients. Secondly, above trend was evidently enhanced when combining with drought stress gradients, in which severe drought amplified facilitative effects, whereas the magnitude of facilitation was relatively weak under well-watered condition. Interestingly, biomass-based facilitation transition did not synchronize with seed-based one, in which occurred in a broader threshold range of water and P gradients. Specifically, total yield, biomass, N and P uptake increased by 0.5%, 4.1%, 1.8% and 2.9% under the sufficient P and water availability, whereas these indicators increased by 25.3%, 18.5%, 20.5% and 21.4% in P and water deficient soils. And the total net effect was positive under all the environmental conditions. Rhizosphere interaction plays a crucial role in facilitation judgment, and the driving mechanism was associated with soil acidification and microbial community promotion under P-deficient condition. Under low soil moisture and available P, soil acidification and lower rhizosphere soil pH of intercropped maize were observed. Rhizosphere phosphatase secretion were significantly activated in P-deficient soils and accelerated the mineralization of soil organophosphorus, and the microbial biomass P was improved for stronger facilitation. Taken together, our findings confirmed the P and water driven facilitation shift along with stress gradients and highlighted the roles of rhizosphere interaction in affecting species diversity advantage. In conclusion, our work provided a relatively full picture for plant facilitation evaluation and more accurate management regarding intercropping productivity.